Pemanfaatan Model Modifikasi Blended Learning dalam Pembelajaran Bahasa Bali pada Masa Pandemi Covid-19 - I Nyoman Miarta Putra (Pramana: Jurnal Hasil Penelitian, 2022)
This study aims to share the best learning experiences during the Covid-19 pandemic. Finding a suitable learning model in the midst of this epidemic, the authors innovate because of government policies that cover the implementation of distance learning. Modifying the learning paradigm of Blended Learning is one of them. Blended learning is a type of learning that combines online and face-to-face instruction. Because the face-to-face learning method cannot be implemented directly, changes must be made. Changes are made on both sides, both online and in person. From packaging subject information to offering discussion space for students to explain elements that are not yet understood, the online side is being modified. The study of small test results was used as a starting point for designing virtual "face to face" learning techniques. Meanwhile, learning takes place informally through Zoom Meeting media at the face-to-face stage. For students who are unable to participate in live learning via Zoom due to network problems or internet limitations, the teacher sends learning videos with small file capacities. Videos are stored in LMS Schoology and can be accessed and downloaded at any time. Modified Blended Learning can be used as a learning technique during the Covid-19 pandemic, according to the findings. In addition, it is known that the education unit requires teachers and students to be trained in the use of digital technology gadgets. School systems thinking must also evolve to recognize that learning can take place outside the classroom and can be accessed from anywhere. The government will be forced to boost free wifi facilities as a result of the implementation of this Blended Learning change. Because we live in the digital era, the internet network plays an important role in helping the teaching and learning process.